What Can the State Do for You?: Relocation allowances and regional subsidies in post-war Sweden. Issue 3 (27th May 2017) - Molinder, Jakob; Ottosson, Jan; Andersson-Skog, Lena; Magnusson, Lars
Abstract : It has been suggested that Swedish policy during the early post-war period was strongly directed towards mobility-increasing expenditures – most notably relocation allowances – aimed at moving labour from north to south. While this view has dominated the academic discussion on labour market policy, there is little direct evidence. We make three claims. First, the relocation allowances have to be evaluated against the regional policy. Second, by doing so we show that the mobility-oriented policy was predominant only for a short period of time: in the early 1970s, there was a decisive shift towards a policy directed at stimulating employment in the north. Third, drawing on this, we revaluate the previous view on policy making in Sweden. Our analysis suggests that the Social Democratic government acted in a voter-maximizing way. The relocation allowances were introduced at the behest of the Trade Union Confederation (LO). The regional subsidies were expanded when voter sentiment turned against the perceived depletion of rural regions. However, this strategy interacted with the political and institutional environment. The new election law in 1970 and political competition from the Centre Party pushed the Social Democrats to shift their policies on regional subsidies.